2022
DOI: 10.1177/10596011221117723
|View full text |Cite
|
Sign up to set email alerts
|

Accent Speaks Louder than Ability: Elucidating the Effect of Nonnative Accent on Trust

Abstract: Nonnative accent often leads to prejudicial judgments. In this paper, we examine the effect of a job candidate’s Mandarin Chinese accent on a hiring manager’s perceptions of trust and the three dimensions of trustworthiness. The results of an online experiment with 179 working adults suggest that speaking with a nonnative accent (vs. no accent) adversely affects hiring decision-makers’ perceptions of trust and the ability dimension of trustworthiness, but not the benevolence and integrity dimensions. We also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The results regarding the impact of accents on listeners’ attitudes and behaviors align with previous research findings. These studies have shown that individuals speaking with an accent are often at a disadvantage in attractiveness ratings, employment opportunities, and customer service evaluations [ 4 , 5 , 19 , 20 , 21 ]. The effect of accent on personal interactions may be attributed to the information conveyed through language pronunciation, which assists individuals in categorizing others into distinct groups [ 22 , 23 ], even though the listeners cannot identify the speaker’s country of origin [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding the impact of accents on listeners’ attitudes and behaviors align with previous research findings. These studies have shown that individuals speaking with an accent are often at a disadvantage in attractiveness ratings, employment opportunities, and customer service evaluations [ 4 , 5 , 19 , 20 , 21 ]. The effect of accent on personal interactions may be attributed to the information conveyed through language pronunciation, which assists individuals in categorizing others into distinct groups [ 22 , 23 ], even though the listeners cannot identify the speaker’s country of origin [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Blacks are often viewed as aggressive and untrustworthy (Cooley & Payne, 2019), while Asians are often cited as the "model minority," which describes them as intelligent, hardworking, and economically successful (Rosette et al, 2018). However, Asians face stereotypes in other areas, such as accents (Geiger et al, 2023) and anti-Asian sentiment as a result of COVID-19 (Dhanani et al, 2023), and they have been shown to be evaluated less favorably than Whites in selection and promotion decisions, particularly for positions involving social skills (Lai & Babcock, 2013).…”
Section: Bias/discrimination Researchmentioning
confidence: 99%